Perancangan Sistem Integrasi Sparepart Menggunakan Aplikasi Macro Visual Basic for Aplication Excel - Angga Yoga Aji Patria; Abidin (Journal of Mandalika Literature, 2024)
This research aims to design a spare part integration system using a VBA Excel application as a solution to expedite the search process in a spare part warehouse in Tangerang. The main problems encountered include lengthy search times due to disorganized layouts and the absence of an adequate support system. The methods used include downtime analysis, redesign of spare part rack layouts, and development of a VBA-based search application. The results show that the proposed system significantly reduces spare part search times and improves the warehouse's operational efficiency (Integration system, spare parts, VBA Excel, efficiency.).